The Cambridge history of sixteenth-century music - Fenlon, Iain,Wistreich, Richard (Cambridge University Press, 2019)
Confessions, identities, and rhetorics of power. Catholic music in the sixteenth century / Robert L. Kendrick ; Lutheranism and Calvinism / Alexander Fisher ; Music and reform in France, England, and Scotland / Magnus Williamson ; Music in the early colonial world / Olivia Bloechl, Melinda Latour ; Music and war / Richard Wistreich – Culture, place, and practice. Urban soundscapes / Iain Fenlon ; Interior spaces for music / Flora Dennis ; The lives of musicians / Richard Wistreich ; Domestic music / Kate van Orden – Institutions, ideas, and the order of nature. Institutions and intellectual life / Giuseppe Gerbino and Inga Mai Groote ; Music theory and pedagogy / Thomas Christensen ; Music and science / Floris Cohen and Jacomien Prins ; Music and magic / Angela Voss
10.1017/9780511675874
Keywords: Aufsatzsammlung; Music